The Relationship between Entrepreneurial Spirit, Motivation, and Entrepreneurial Interest: A Literature Review - Novi Susanti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to examine the relationship between entrepreneurial spirit, entrepreneurial motivation, and entrepreneurial intention based on findings from previous studies. The method employed is a literature review using a library research approach through the systematic exploration of scholarly sources from Google Scholar and other academic databases. The findings indicate that entrepreneurial spirit is closely associated with entrepreneurial motivation, as individuals who demonstrate creativity, independence, and a willingness to take risks tend to possess stronger internal drives to initiate entrepreneurial activities. In addition, entrepreneurial spirit is also correlated with entrepreneurial intention. The review further reveals that entrepreneurial motivation plays a reinforcing role in strengthening individuals’ intentions to pursue entrepreneurship. Overall, entrepreneurial spirit, motivation, and intention form an interrelated framework in the process of shaping an individual’s entrepreneurial orientation.